Life course sun exposure and risk of prostate cancer: population-based nested case-control study (ProtecT) and meta-analysis - Gilbert, Rebecca (2009)
There is currently no means of primary prevention for prostate cancer. Increased exposure to ultraviolet-radiation may be protective, but the literature is inconclusive. We investigated associations of life-course exposure to sunlight with prostate cancer. The study design was a UK-wide nested case-control study, based on 1,020 PSA-detected cases and 5,044 matched population controls and a systematic review with meta-analysis. Men with olive/brown skin (OR= 1.47; 95% CI: 1.00 to 2.17), men who burnt rarely/never (OR= 1.11; 0.95 to 1.29) and men with the lowest levels of intense sun exposure in the 2 years prior to diagnosis (OR = 1.24; 1.03 to 1.50) had an increased prostate cancer risk. However, amongst men with prostate cancer, spending less time outside was associated with a reduced risk of advanced cancer (OR = 0.49; 0.27 to 0.89) and high Gleason grade (OR = 0.62; 0.43 to 0.91), and men who burnt rarely/never had a reduced risk of advanced cancer (OR = 0.71; 0.47 to 1.08). The meta-analysis provided weak evidence that men with the lowest (versus highest) sunlight exposure had an increased prostate cancer risk (4 studies, random-effects pooled relative risk = 1.13; 0.98 to 1.29) and higher advanced or fatal prostate cancer risk (6 studies, random-effects pooled relative risk = 1.14; 0.98 to 1.33). Our data and meta-analyses provide limited support for the hypothesis that increased exposure to sunlight may reduce prostate cancer risk. The findings warrant further investigation because of their implications for vitamin D chemoprevention trials.